Making Students’ Mathematical Arguments Explicit - Kosko, Karl Wesley; Guilford, Elizabeth (Ohio Journal of School Mathematics, 2018)
Elementary students are expected to construct viable arguments with increasing sophistication as they progress through schooling. This article describes students’ progression as different shifts from tacit to explicit mathematical talk and writing. We include a resource for teachers’ to aid in evaluating and understanding children’s argumentation in K-5.